1992
DOI: 10.1007/bf00180280
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of lymphocyte subsets and expression of activation markers in response to immunotherapy with galactoside-specific lectin from mistletoe in breast cancer patients

Abstract: Cellular aspects of the immunomodulating activity of the galactoside-specific lectin from mistletoe (ML-1) were investigated in 10 cancer patients. Regular subcutaneous injections (4 weeks) of the optimal dosis of ML-1 (1 ng per kg body weight, twice a week) yielded notable increases in the apparent numbers of certain lymphocyte subsets [pan T cells; helper T cells; natural killer (NK) cells] which are generally believed to be involved in antitumor immunity. Moreover, ML-1 administration resulted in an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
6

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(23 citation statements)
references
References 14 publications
0
17
0
6
Order By: Relevance
“…Mistletoe extracts are often used as complementary cancer treatment in addition to standard chemotherapy and radiation treatment and are reported to have an immunostimulatory and pain-relieving effect (Hajto et al, 1989;Beuth et al, 1992;Heiny et al, 1998;Stein and Berg, 1998;Ernst and Cassileth, 1999). A direct antitumour effect of mistletoe has been linked to the specific components lectin I -III that can induce apoptosis in various transformed cell lines, in particular in tumour cells of lymphoid origin.…”
mentioning
confidence: 99%
“…Mistletoe extracts are often used as complementary cancer treatment in addition to standard chemotherapy and radiation treatment and are reported to have an immunostimulatory and pain-relieving effect (Hajto et al, 1989;Beuth et al, 1992;Heiny et al, 1998;Stein and Berg, 1998;Ernst and Cassileth, 1999). A direct antitumour effect of mistletoe has been linked to the specific components lectin I -III that can induce apoptosis in various transformed cell lines, in particular in tumour cells of lymphoid origin.…”
mentioning
confidence: 99%
“…ML-I is a component of a commercially available mistletoe extract with immunostimulating potency applied for the treatment of human cancer [7]. This immunomodulating capacity has recently been attributed to the presence of ML-I in the extract [8].…”
Section: Introductionmentioning
confidence: 99%
“…The general pathway(s) of activation of these mechanisms are still unknown, but specific mistletoe lectin-carbohydrate (cell glycoconjugate) interactions appear to be the effector system involved in eliciting such an immune response [14]. Controlled increases of these non-specific defence mechanisms may induce clinically beneficial immunomodulation in the treatment of cancer [7]. Accordingly, the detailed chemical structure of ML-I is crucial to elucidate its immunomodulatory capacity and for the design of more effective therapeutic substances.…”
Section: Introductionmentioning
confidence: 99%
“…Beuth et al [50] have demonstrated that ML-I enhanced expression of HLA-DQ on B cells. In vivo experiments have demonstrated that during treatment with MLs, anti-ML antibodies of IgG and IgE isotype are produced.…”
Section: Discussionmentioning
confidence: 99%